2019
DOI: 10.1186/s13023-019-0999-3
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of facial emotion recognition and visual information processing in adult patients with classical galactosemia

Abstract: Background Classical galactosemia (CG) is due to a severe deficiency of the galactose-1-phosphate uridyl-transferase (GALT), the main enzyme of galactose metabolism. Even early introduction of galactose-restricted diet fails to prevent long-term complications, including cognitive impairment, neurological and psychiatric problems, osteoporosis, premature ovarian failure and infertility. Detailed neuropsychological phenotyping is needed in order to better understand the relevant neurodevelopmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Future research is needed to understand poor social functioning in CG other than from deficits in the autism spectrum. A recent study found impaired visual information processing and facial emotion recognition in CG patients, which might contribute to the difficulties in social interactions observed in patients [22].…”
Section: Discussionmentioning
confidence: 98%
“…Future research is needed to understand poor social functioning in CG other than from deficits in the autism spectrum. A recent study found impaired visual information processing and facial emotion recognition in CG patients, which might contribute to the difficulties in social interactions observed in patients [22].…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Patients differ in severity and profile of the cognitive difficulties but impairments in attention and information processing speed, (working) memory, visuospatial functioning, cognitive flexibility and social cognition seem to be most prevalent. [4][5][6][7] These cognitive difficulties have a negative impact on the quality of life of CG-patients. 8 A recurrent question is whether the cognitive impairments in CG are stable throughout life or progress with age.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment does not prevent long-term complications such as premature ovarian failure, neurological manifestations, behavioral alterations, and decreased bone mineral density which have been reported to occur with different degrees of severity [2,11]. Several publications suggest that such complications may appear independent of the age of onset and treatment adherence [2,[11][12][13][14][15][16][17]. Over time, patients may have difficulties in learning and language (verbal dyspraxia and dysarthria), also they frequently develop tremors and, to a lesser extent, ataxia and dystonia [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in adulthood, patients develop a complex neuropsychological phenotype, which appears more severe in men, and that is characterized by anxiety, depression, and difficulties to recognize complex facial emotions such as anger, surprise, fear, and disgust [18]. Together, these clinical signs affect patient's quality of life and can contribute to the disturbances in social interaction reported in this population [15,[18][19]. All the above demonstrates that the exact pathological mechanisms involved in the disease are still unknown, despite the development of animal models; in vitro and descriptive studies; as well as interventions in cohorts of patients with classical galactosemia, have helped to strengthen our understanding of different molecular, clinical, and metabolic aspects of the disease [9,14,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%